Evaluation Of PKL Alternative in TITL Major at Vocational High School - Fadillah Husni; ridwan ridwan; sukardi sukardi; ambiyar ambiyar (Patria Artha Technological Journal, 2021)
This study aims to evaluate the implementation of PKL Alternatif at Vocational High School 1 West Sumatera, The evaluation of PKL Alternatif was seen from aspects of context, input, activities, output and outcome faced in the implementation of the PKL Alternatif. The research method used is a combination of Sequental Explanatory design methods, combining quantitative research method using quetionnaires  or questionnaires and qualitative with interviews sequence, where data analysis technique use the percentage of respondent achievement levels TCR test for quantitative data and for qualitative data using techniques Miles and Huberman’s data analysis models are data reduction, data display and conclussion or verification. The result showed that implementation PKL Alternatif at Vocational High School 1 West Sumatera of TITL Major as a whole included: Evaluation of context obtained a standard average score of 81,18% well. Evaluation of input obtained a standard average score of 78,30% enough. Evaluation of activities obtained a standard average score of 75,56% enough. Evaluation of output obtained a standard average score of 81,30% well. Evaluation of outcome obatained standard average score of 79,26% enough. Based on the findings of this study, it concluded that the PKL Alternatif program in 2020 at Vocational High School 1 West Sumatera TITL Major was still in the sufficient category, needing to be improved for each aspect.